Formulation of furosemide solid dispersion with micro crystalline cellulose for achieve rapid dissolution - Rajanikant C Patel; Rajesh A Keraliya; Madhabhai M Patel; Natvarlal M Patel (Wolters Kluwer Medknow Publications, 2010)
Furosemide, a weekly acidic, loop diuretic drug indicated for treatment of edema and hypertension having high permeability through stomach. It is practically insoluble in gastric fluid (0.006 mg/ mL) and having highly permeability through stomach but due to its solubility limitation it can't enter into systemic circulation. It was logically decided to design experiment, so as to achieve the set objectives. Attempt was made to prepare solid dispersion of furosemide with Poly ethylene glycol (PEG) 6000 containing microcrystalline cellulose (MCC) as adsorbent which would dissolve completely in less than 30 minutes (target selected by considering minimum gastric empting time). Microcrystalline cellulose converted sticky dispersion in to free flow powder hence increase surface area which responsible for dissolution improvement. Factorial design was applied to optimize formulation. Amount of poly ethylene glycol 6000 and microcrystalline cellulose were selected as an Independent variable while angle of repose and T100% were selected as dependent variable. Attempts for dissolution rate of furosemide improve bioavailability and consequently dose reduction would possible.